2016
DOI: 10.1242/jeb.141614
|View full text |Cite
|
Sign up to set email alerts
|

Jaw morphology and fighting forces in stag beetles

Abstract: The jaws of different species of stag beetles show a large variety of shapes and sizes. The male jaws are used as weapons in fights, and they may exert a very forceful bite in some species. We investigated in 16 species whether and how the forcefulness of their bite is reflected in their jaw morphology. We found a large range of maximal muscle forces (1.8-33 N; factor of 18). Species investing in large bite muscles also have disproportionately large jaw volumes. They use this additional jaw volume to elongate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…These determine the shape of the head because a long input lever means that the anterior end of the head must be wider, and the attachment for the jaw closer muscles is at the rear of the head, so larger muscles will be associated with the posterior of the head being enlarged. This relationship between mandible size and head size is also supported by an interspecific comparison which found that species with large heads also have relatively large mandibles 37 . Given this, the clear difference found between morphs of the tri- and tetramorphic species in the geometric morphometric analyses makes sense.…”
Section: Discussionmentioning
confidence: 58%
“…These determine the shape of the head because a long input lever means that the anterior end of the head must be wider, and the attachment for the jaw closer muscles is at the rear of the head, so larger muscles will be associated with the posterior of the head being enlarged. This relationship between mandible size and head size is also supported by an interspecific comparison which found that species with large heads also have relatively large mandibles 37 . Given this, the clear difference found between morphs of the tri- and tetramorphic species in the geometric morphometric analyses makes sense.…”
Section: Discussionmentioning
confidence: 58%
“…The mandible length (ML), head width (HW) and elytra length (EL) of the beetles were measured to the nearest of 0.01 mm using a digital calliper (99MAD027M1, Mitutoyo, Kanagawa, Japan). Mandible length was the average linear distance between the distal tip of the mandible and the axis of the mandibular joint of the two mandibles [7,8,29]; HW was the linear distance between the tips of the protrusions anterior to the eyes; EL was the linear distance between the posterior ends of the scutellum and the elytra. These three measurements were obtained on the day on which the beetles were collected in the field or the 21st day after the eclosion of the beetles reared in the laboratory.…”
Section: Morphological Measurementsmentioning
confidence: 99%
“…This trade-off is common in nature and often affects the intricate balance between survival and reproductive prowess, such as fecundity 2 4 and male weaponry and ornaments. These latter traits are large, extravagant structures that are energetically costly to develop 5 , 6 but increase males’ reproductive success by enhancing their fighting abilities and/or appeal to female mate choice 7 , 8 . Males of the stag beetle Cyclommatus metallifer , for example, are well known to express extremely large and conspicuous weapons that improve mating success, but come at costs in terms of wing size and flight muscles 9 .…”
Section: Introductionmentioning
confidence: 99%